Compassion and Beyond - Crisp, Roger (Ethical theory and moral practice, 2008)
This paper is a discussion of the emotion of compassion or pity, and the corresponding virtue. It begins by placing the emotion of compassion in the moral conceptual landscape, and then moves to reject the currently dominant view, a version of Aristotelianism developed by Martha Nussbaum, in favour of a non-cognitive conception of compassion as a feeling. An alternative neo-Aristotelian account is then outlined. The relation of the virtue of compassion to other virtues is plotted, and some doubts sown about its practical significance.